Anchoring Co3O4 nanoparticles on MXene for efficient electrocatalytic oxygen evolution - Lu, Yi; Fan, Deqi; Chen, Zupeng; Xiao, Weiping; Cao, Cancan; Yang, Xiaofei (Science bulletin (Beijing), 2020)
[Display omitted] Rational design and controllable synthesis of efficient electrocatalysts for water oxidation is of significant importance for the development of promising energy conversion systems, in particular integrated photoelectrochemical water splitting devices. Cobalt oxide (Co3O4) nanostructures with mixed valences (II,III) have been regarded as promising electrocatalysts for the oxygen evolution reaction (OER). They are able to promote catalytic support of OER but with only modest activity. Here, we demonstrate that the OER performance of cubic Co3O4 electrocatalyst is obviously improved when they are anchored on delaminated two-dimensional (2D) Ti3C2 MXene nanosheets. Upon activation the overpotential of the hybrid catalyst delivers 300 mV at a current density of 10 mA cm−2 in basic solutions, which is remarkably lower than those of Ti3C2 MXene and Co3O4 nanocubes. The strong interfacial electrostatic interactions between two components contribute to the exceptional catalytic performance and stability. The enhanced OER activity and facile synthesis make these Co3O4 nanocubes-decorated ultrathin 2D Ti3C2 MXene nanosheets useful for constructing efficient and stable electrodes for high-performance electrochemical water splitting.